2023
DOI: 10.1001/jamaoto.2022.4839
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human Papillomavirus Status With Suicide Risk Among Patients With Head and Neck Cancer

Abstract: ImportanceHuman papillomavirus (HPV) is strongly associated with head and neck cancer, and HPV status is considered a prognostic factor. Being a sexually transmitted infection, HPV-related cancers may have greater risk of stigma and psychological distress; however, the potential association of HPV-positive status with psychosocial outcomes, such as suicide, is understudied in head and neck cancer.ObjectiveTo investigate the association between HPV tumor status and suicide risk among patients with head and neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Missing HPV data was imputed through Multiple Imputation Chained Equations 23 (50x) Logistic Regressions with histology, grade, schema as predictors 17,24,25 . Given that the level of missingness varies over time (∼70% in 2010 and 20% in 2017) 22 , and high proportion of estimated HPVa OPC (>70%), we do not restrict the sample to HPV positive cases but instead add imputed HPV codes to all models.…”
Section: Methodsmentioning
confidence: 99%
“…Missing HPV data was imputed through Multiple Imputation Chained Equations 23 (50x) Logistic Regressions with histology, grade, schema as predictors 17,24,25 . Given that the level of missingness varies over time (∼70% in 2010 and 20% in 2017) 22 , and high proportion of estimated HPVa OPC (>70%), we do not restrict the sample to HPV positive cases but instead add imputed HPV codes to all models.…”
Section: Methodsmentioning
confidence: 99%
“…The specialized data file includes a clinically validated variable indicating the HPV etiology (HPV in situ hybridization, tissue polymerase chain reaction, in situ hybridization for E6/7 RNA, real‐time polymerase chain reaction for E6/7 RNA) of each HNC tumor within the following HNC sites: Lip, Hypopharynx, Nasopharynx, Oropharynx, Pharyngeal Tonsil, Pharynx Other, Palate Soft, Tongue Base, Gum and Other Mouth, and Other Oral Cavity 30 . Following established practice, missing HPV‐status was imputed with data on tumor grade, histology, site, behavior, and encrypted census tract‐level socioeconomic indicators via a logistic regression model through Multiple Imputation Chained Equations 31–38 . This specialized data includes cancer diagnoses for year 2010–2016.…”
Section: Methodsmentioning
confidence: 99%
“…30 Following established practice, missing HPV‐status was imputed with data on tumor grade, histology, site, behavior, and encrypted census tract‐level socioeconomic indicators via a logistic regression model through Multiple Imputation Chained Equations. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 This specialized data includes cancer diagnoses for year 2010–2016. Because adults over age 65 could benefit from access to Medicaid dental coverage, the analytical sample includes adults between ages 30–84.…”
Section: Methodsmentioning
confidence: 99%
“…Smaller studies have backed many of the associations while adding further nuance to the overall findings. One recent report, for example, found that the risk of suicide is roughly equivalent with human papillomavirus (HPV)–independent and HPV‐associated head and neck tumors 6 . Dr Richmon, however, warns that different factors may be contributing to the risk for each group.…”
Section: A Lack Of Reliable Predictorsmentioning
confidence: 99%
“…One recent report, for example, found that the risk of suicide is roughly equivalent with human papillomavirus (HPV)independent and HPV-associated head and neck tumors. 6 Dr Richmon, however, warns that different factors may be contributing to the risk for each group. The traditional group of patients with HPV-independent head and neck cancers tends to be older, have higher rates of tobacco and alcohol use, and carry other comorbidities.…”
Section: A Disturbing Link Between Cancer and Suicidementioning
confidence: 99%